Red-capped mangabeys (Cercocebus torquatus) adapt their interspecific gestural communication to the recipient’s behaviour - Aychet, Juliette; Pezzino, Pablo; Rossard, Arnaud; Bec, Philippe; Blois-Heulin, Catherine; Lemasson, Alban (Scientific reports, 2020)
Sensitivity to recipient’s attention and responsiveness are critical markers of intentional communication. Although previous research showed that ape gestures can be intentional, few studies have yet addressed this question concerning monkeys. Here, we characterise the effect of a recipient’s presence, attentional state and responsiveness on the interspecific gestural communication of captive red-capped mangabeys ( Cercocebus torquatus ). Previous reports showed that they produced learnt begging gestures towards a human recipient preferentially when the latter was facing them. We used here a novel setup that allows subjects to move around an experimenter and to use different modalities (visual and acoustic) to communicate. We found that when the recipient was not facing them, mangabeys moved to a position in the visual field of their recipient rather than using attention-getters. Interestingly, unlike apes, they did not elaborate their communication visually or acoustically when the experimenter did not respond favourably to their begging. However, our results may suggest that begging gestures were goal-directed, since mangabeys inhibited them when the experimenter was not available to answer immediately (i.e. give a reward). Overall, red-capped mangabeys’ interspecific visual communication presented intentionality features, but their use of begging gestures was less flexible than that of great apes in similar situations.